Localization and function of a Plasmodium falciparum protein (PF3D7_1459400) during erythrocyte invasion - Amlabu, Emmanuel; Nyarko, Prince B.; Opoku, Grace (Experimental Biology and Medicine, 2020)
Nearly 60% of Plasmodium falciparum proteins are still uncharacterized and their functions are unknown. In this report, we carried out the functional characterization of a 45 kDa protein (PF3D7_1459400) and showed its potential as a target for blood stage malaria vaccine development. Analysis of protein subcellular localization, native protein expression profile, and erythrocyte invasion inhibition of both clinical and laboratory parasite strains by peptide antibodies suggest a functional role of PF3D7_1459400 protein during erythrocyte invasion. Also, immunoreactivity screens using synthetic peptides of the protein showed that adults resident in malaria endemic regions in Ghana have naturally acquired plasma antibodies against PF3D7_1459400 protein. Altogether, this study presents PF3D7_1459400 protein as a potential target for the development of peptide-based vaccine for blood-stage malaria.
Keywords: University of Ghana; WACCBIP_NCDS; Damata Ibrahim-Dey; Philip Ilani; Henrietta Mensah-Brown1; Plasmodium falciparum; malaria vaccine; erythrocyte invasion; peptide antibodies; naturally acquired antibodies